Mild abnormalities in liver histology associated with chronic hepatitis: distinction from normal liver histology. Issue 11 (November 1997) - Kay, E W; O'Dowd, J; Thomas, R; Alyusuf, R; Sachithanandan, S; Robinson, R; Walsh, C B; Fielding, J F; Leader, M B
Abstract : BACKGROUND: Chronic hepatitis C virus infection associated with contaminated anti-D immunoglobulin has become an issue of recent concern. The clinical course of chronic hepatitis C infection is unpredictable and histological assessment is felt to be the most reliable means of assessing disease status. Semiquantitative scoring systems have been devised, which assess degree of necroinflammatory disease activity (grade) and extent of disease progression with fibrosis (stage) in chronic hepatitis. Often, using these systems, biopsies of anti-D associated chronic hepatitis C cases show mild changes only, with low scores. The significance of these low scores is uncertain. AIMS: To evaluate the significance of low scores in chronic hepatitis. METHODS: Liver biopsies were assessed from two groups of patients in whom liver histology would be expected to be normal: 30 cases of Gilbert's syndrome and 13 necropsy cases of young people (< 45 years) with no history or risk factors for liver disease. These biopsies were scored using the histological activity index of Knodell et al and its recent modification (separation of scores for grade and stage) by Ishak et al. RESULTS: Twenty of 30 cases of Gilbert's syndrome and 11 of the 13 necropsy cases had chronic hepatitis scores of 1 or 2, whereas only eight cases of Gilbert's and two necropsy cases had scores of 0. The remaining two Gilbert's cases had scores of 3 and 5. Similar results were found using both the histological activity index of Knodell et al and the method of Ishak et al. CONCLUSION: The finding of low but positive scores using these systems in people with normal liver histology questions the reliability and significance of finding such scores in patients with chronic hepatitis and is of particular concern in the evaluation of chronic hepatitis C infection.